2002
DOI: 10.1074/jbc.m108727200
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Clustering of Platelet GP Ib-IX Complexes Leads to Up-regulation of the Adhesive Function of Integrin αIIbβ3

Abstract: Binding of von Willebrand factor (VWF) to GPThe GP Ib-IX-V complex consists of four leucine-rich, type I transmembrane polypeptides, two linked by disulfide bonds (GP Ib␣ and GP Ib␤), and two linked noncovalently (GP IX and GP V). The postulated subunit stoichiometry is 2:2:2:1, respectively (1-3), and each platelet expresses ϳ25,000 copies of GP Ib (4, 5). Interaction between GP Ib-IX and its principal ligand, von Willebrand factor (VWF), 1 mediates platelet capture onto exposed extracellular matrices under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 82 publications
3
68
0
2
Order By: Relevance
“…Based on the fact that the spherical shape of CHO cell only allows a small contact region between cells and surface, it is likely that a bundle of GP Ib-IX molecules in one or several GEMs provides the forces to mediate the translocation of the cells. In agreement, it has been suggested that the GEM localization of GP Ib␣ may increase the local density of GP Ib␣ (clustering) (9,49,50), thereby providing short lived GP Ib-IX/ vWf bonds at one time for slower rolling. Thus, dissociation of GP Ib␣ from these GEMs could decrease the local density of GP Ib␣ and reduce the multivalence of GP Ib-IX/vWf bonding and as a result, impair the resistance of the GP Ib-IX-expressing CHO cells to high shear force and cause faster movement of the cells under flow (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Based on the fact that the spherical shape of CHO cell only allows a small contact region between cells and surface, it is likely that a bundle of GP Ib-IX molecules in one or several GEMs provides the forces to mediate the translocation of the cells. In agreement, it has been suggested that the GEM localization of GP Ib␣ may increase the local density of GP Ib␣ (clustering) (9,49,50), thereby providing short lived GP Ib-IX/ vWf bonds at one time for slower rolling. Thus, dissociation of GP Ib␣ from these GEMs could decrease the local density of GP Ib␣ and reduce the multivalence of GP Ib-IX/vWf bonding and as a result, impair the resistance of the GP Ib-IX-expressing CHO cells to high shear force and cause faster movement of the cells under flow (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…CHO cells have been used frequently by a number of established researchers to model aspects of platelet signaling. [21][22][23][24][25][26] A wealth of knowledge concerning platelet-related events has been derived from studies in this particular host system. For example, mutational studies of plateletspecific components such as GPIIb/IIIa, GPVI, and GPIb-IX, are virtually impossible to perform in platelets using current molecular biologic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…We chose CHO cells as our mammalian expression model, as these cells have been widely used as a simplified model to study platelet-related events, [21][22][23][24][25][26] and thus overexpressed recombinant human CIB in CHO cells to better understand its physiologic role. Although CHO cells are not of human origin, the fact that CIB is so highly conserved among species ( Figure 1A) suggests that overexpression of human CIB may complement the endogenous signaling.…”
Section: Overexpression Of Cib Induces Cell Migrationmentioning
confidence: 99%
“…Ligation of platelet GPIb to endothelial cell von Willebrand factor during platelet rolling lead to activation of platelet integrin (Kasirer-Friede et al, 2002). Integrins are ubiquitous transmembrane / heterodimers that mediate cell-matrix and cell-cell interactions (Bennet, 2005).…”
Section: Tight Adhesion Of Platelet To Endothelial Cell Surfacementioning
confidence: 99%